Efficacy and Complication Rates of Percutaneous Vertebroplasty and Kyphoplasty in the Treatment of Vertebral Compression Fractures: A Retrospective Analysis of 280 Patients - Cerny, Jan; Soukup, Jan; Petrosian, Kadzhik; Loukotova, Lucie; Novotný, Tomáš (Journal of clinical medicine, 2024)
Background: Percutaneous vertebroplasty (PVP) and kyphoplasty (PKP) are established methods in the treatment of vertebral compression fractures (VCFs). In our manuscript, the target was to evaluate the efficacy of PVPs/PKPs and to determine the implications of potential periprocedural complications. Methods: 280 patients, specifically 194 women (69.3%) and 86 men (30.7%), were enrolled. We used the AO spine fractures classification and the Yeom classification to determine the subtype of cement leakage. Only single-level VCFs of the thoracic or lumbar spine were included. Visual analogue scale (VAS) was assessed preoperatively and regularly after the surgery. Vertebral compression ratio (VBCR) was used to determine postoperative vertebral body collapse. Results: We recorded 54 cases (19.3%) of cement leakage. There was a significant decrease in mean VAS scores (6.82-0.76 in PVPs, 7.15-0.81 in PKPs). The decrease in VBCR was greater in the VP group (4.39%; 84.21-79.82) compared to the KP group (1.95%; 74.36-72.41). Conclusions: No significant difference in the risk of cement leakage when comparing KPs and VPs was found. VPs and KPs provide rapid and significant pain relief in patients with VCFs. Clinically relevant complications of VPs and KPs are rare. Kyphoplasties prevent further vertebral body collapse more effectively compared to vertebroplasties.